The development of industrial infrastructure during the industrial modernization of Russia - Yu. Gedgafova, Irina; H. Shogentsukova, Zalina; A. Efendieva, Genrietta; S. Sijajeva, Svetlana; M. Mirzoeva, Janna (International Journal of Engineering and Technology, 2018)
The modern phase of the national economic and financial crisis clearly shows the world economy institutional transformation, increasingly reducing the competitiveness of the Russian industrial complex in particular. According to retrospective analysis carried out by specialists in techno-economic paradigms, this kind of changes occur primarily when the role of the dominant energy resource and, subsequently, the role of other production and infrastructure resources changes in all sectors, including industry. In this regard, the effectiveness of the aggregate production infrastructures of industrial enterprises, hereinafter referred to as the industrial infrastructure, is of theoretical and practical importance at the current stage of economic transformation, and therefore is an appropriate topic for a research. In this article, the authors tried to develop the theoretical issues of modern trends in the industrial infrastructure development, to define methods and mechanisms for its implementation. The article presents the structure of industrial enterprises infrastructure, identifies the problems in managing the production structure and suggests ways to solve the identified problems. Â